The Importance of Accurate Boundary Condition in Obtaining Reliable Shearing Stresses on a Torsional Finite Element Simulation - Martins, J. A.; Romao, E. C. (Engineering, Technology & Applied Science Research, 2022)
Many combustion engines and electric motors drive machines or equipment by turning a shaft and thus producing work. As a relevant part of a machine principle, torque transference deserves deep analysis regarding the techniques that determine precisely the Finite Element (FE) boundary conditions that are to be applied. This work presents a shaft loaded with a torque that causes torsion and results in shear stresses in the shaft material. In this context, when designing and calculating a shaft to transfer torque, virtual analysis like FE Analysis (FEA) must replicate the reality as accurately as possible. Indeed, slight changes in load and constraint in a virtual simulation can produce considerably different shear stresses and unrealistic results. This paper aims to demonstrate how distinct boundary conditions for the same torque transference can result in very different results when a simulation does not comply with reality. The results showed the importance of being very attentive when applying loads and constraints on a shaft under torsion while calculating it via FEA.